Design and Implementation of Home Automation Based on Voice Recognition System and IOT using Node MCU - Haithem Ali; Hend Albighdadi (المجلة الليبية للدراسات الأكاديمية المعاصرة, 2025)
Automation has become a common process at this time, as automation reduces the consumer time to carry out tasks and work to reduce human risks. Given the development of technology, where Android applications are developed periodically to help us in several ways to facilitate life and raise the suffering of the segments of society, we mention from them in our research the elderly and the disabled, as these segments suffer when they alone at home are operating electrical appliances. For the development of sound processing technology by converting it to the texts, this feature was used to control home appliances remotely, as our study combines all these things to provide a home automation system based on an accurate controller and the smartphone is active. Through the Internet, users of this system will be able to control of each device in their homes using voice commands. The Android smartphone, which is almost the choice of everyone these days, is all that the user needs in this project to control of appliances. The practical results show that the user was able to use audio orders effectively using the Android application to play home appliances in actual time.